Predicting Driver's Intention Based on Own Vulnerability: A Social Interaction Process between Road Users at an Intersection in Japan12. (11th November 2015) - Kinosada, Yasunori; Usui, Shinnosuke
Abstract: When road users predict the future movement of an approaching vehicle at an intersection, they need to consider not only the physical environment but also the predicted behavioral intention of the approaching driver. In the present experiments, we asked participants to imagine how a vehicle would approach in a natural traffic environment. In Experiment 1, participants estimated the time‐to‐contact with an approaching vehicle as longer when they were physically vulnerable. In Experiment 2, we confirmed that differences in participants' eye height did not explain the findings of Experiment 1. In Experiment 3, we asked participants to indicate the last possible moment at which they could cross an intersection in front of an approaching vehicle. Participants left a shorter safety margin when they were more physically vulnerable than the approaching vehicle. The results indicate that road users' perceived vulnerability is a cue for them to trust the approaching driver's intention to decelerate. This viewpoint is important for interventions to prevent unrealistic trust that an approaching vehicle will avoid an accident and subsequent trust‐based behaviors.